Biological function, mediate cell death pathway and their potential regulated mechanisms for post-mortem muscle tenderization of PARP1: A review - Li, Rong; Luo, Ruiming; Luo, Yulong; Hou, Yanru; Wang, Jinxia; Zhang, Qian; Chen, Xueyan; Hu, Lijun; Zhou, Julong (Frontiers in Nutrition, 2022)
Tenderness is a key attribute of meat quality that affects consumers' willingness to purchase meat. Changes in the physiological environment of skeletal muscles following slaughter can disrupt the balance of redox homeostasis and may lead to cell death. Excessive accumulation of reactive oxygen species (ROS) in the myocytes causes DNA damage and activates poly ADP-ribose polymerase 1 (PARP1), which is involved in different intracellular metabolic pathways and is known to affect muscle tenderness during post-slaughter maturation. There is an urgent requirement to summarize the related research findings. Thus, this paper reviews the current research on the protein structure of PARP1 and its metabolism and activation, outlines the mechanisms underlying the function of PARP1 in regulating muscle tenderness through cysteine protease 3 (Caspase-3), oxidative stress, heat shock proteins (HSPs), and energy metabolism. In addition, we describe the mechanisms of PARP1 in apoptosis and necrosis pathways to provide a theoretical reference for enhancing the mature technology of post-mortem muscle tenderization.